2011
DOI: 10.1007/s10182-011-0174-1
|View full text |Cite
|
Sign up to set email alerts
|

Level and change of group-focused enmity in Germany: unconditional and conditional latent growth curve models with four panel waves

Abstract: In this study we investigate and explain the level and change of six elements of group-focused enmity (GFE; see Zick et al. 2008) in Germany between 2002 and 2006: racism, xenophobia, antiSemitism, homophobia, exclusion of homeless people and support for rights of the established. For the data analysis, a representative 4-year panel study of the adult non-immigrant German population collected during the years 2002-2006 is used, and the development of each GFE component is tested by using an unconditional secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
12
0
2
Order By: Relevance
“…In the ten year-project employing large probability samples of the German population (Zick et al, 2008) the pattern of generalized prejudices has been repeatedly shown empirically (e.g. Davidov et al, 2010). In a cultural comparison study for eight European countries, the researchers found empirical support for the generalized syndrome of GFE as a second-order factor in all examined countries (Zick et al, 2011).…”
mentioning
confidence: 95%
“…In the ten year-project employing large probability samples of the German population (Zick et al, 2008) the pattern of generalized prejudices has been repeatedly shown empirically (e.g. Davidov et al, 2010). In a cultural comparison study for eight European countries, the researchers found empirical support for the generalized syndrome of GFE as a second-order factor in all examined countries (Zick et al, 2011).…”
mentioning
confidence: 95%
“…Specific forms of prejudice, however, cannot entirely be described as a general prejudiced or authoritarian personality structure. Next to a general component, important outgroupspecific variance still remains unexplained (Akrami et al, 2011;Davidov, Thörner, Schmidt, Gosen, & Wolf, 2011). In this paper, we argue that including contextual factors in the model of generalized prejudice can offer additional explanatory power.…”
Section: Structure Of Prejudicementioning
confidence: 68%
“…Besides finding support for a second order-factor for several prejudice elements (the latent variable 'GFE'), the analyses demonstrated the common core of the syndrome by showing its stability over time and by analysing its causes and consequences (e.g. Davidov et al, 2011). In a cultural comparison study for eight European countries, the researchers found empirical support for the generalized syndrome of GFE as a second-order factor in all examined countries (Zick et al, 2011).…”
Section: Fundingmentioning
confidence: 99%